Ways of innovative development of enterprises of the energetic industry of Ukraine influencing energy reform - Mironenko, Mykola A.; Мироненко, Микола Андрійович; Shramko, Inna I.; Шрамко, Інна Іванівна; Kolisnik, Olga A.; Колісник, Ольга Андріївна (Faculty of Architecture, Civil Engineering and Wyższej Szkoły Technicznej w Katowicach, 2018)
The article deals with the search of ways of innovative development of enterprises in the energy market of Ukraine under the influence of its reformation. The easiest way is to change the tariff setting system. But this way is now too politicized. Also, we should not forget about the alternative energy market. Therefore, in the work the specifics of the domestic solar and bioenergy market are analyzed on the example of Kherson and Poltava regions. Proven ability of this market in the next 3-5 years. A step-by-step algorithm for the output of this energy market is presented. У статті розглядаються питання пошуку шляхів інноваційного розвитку підприємств на енергетичному ринкові України під впливом його реформування. Найпростіше – зміна системи тарифоутворення. Але цей шлях нині надто політизований. Також не слід забувати про ринок альтернативної енергетики. Тому в роботі проаналізовано специфіку вітчизняного ринку сонячної та біоенергетики на прикладі Херсонської та Полтавської областей. Доведено перспективність цього ринку в найближчі 3-5 років. Подано покроковий алгоритм виходу на цей ринок енергетичного підприємства.
Шляхи інноваційного розвитку підприємств енергетичної галузі України під впливом реформ енергоринку
Keywords: innovation; інновації; energy company; енергетична компанія; tariff formation; тарифоутворення; alternative energy; альтернативна енергетика; bioenergy; біоенергетика; market; ринок